2020
DOI: 10.3390/toxics8030053
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effects on Lung Function in Community Members Following Exposure to Hazardous PM2.5 Levels from Wildfire Smoke

Abstract: Extreme wildfire events are becoming more common and while the immediate risks of particulate exposures to susceptible populations (i.e., elderly, asthmatics) are appreciated, the long-term health effects are not known. In 2017, the Seeley Lake (SL), MT area experienced unprecedented levels of wildfire smoke from July 31 to September 18, with a daily average of 220.9 μg/m3. The aim of this study was to conduct health assessments in the community and evaluate potential adverse health effects. The study resulted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…This continues to be an area that is not well understood as only limited studies have explored long-lasting or delayed effects of smoke on health. Some have identified increased incidence of influenza (47) and impaired lung function (48) for months to years after a fire event. Canberra had experienced a severe bushfire in January 2003 and a survey 3 years after this disaster found that for over half the survey respondents (56.4%, n = 272) the bushfire did not have a lasting effect on their overall health and 2.5% (n = 12) reported that their overall health was better than before (18).…”
Section: Discussionmentioning
confidence: 99%
“…This continues to be an area that is not well understood as only limited studies have explored long-lasting or delayed effects of smoke on health. Some have identified increased incidence of influenza (47) and impaired lung function (48) for months to years after a fire event. Canberra had experienced a severe bushfire in January 2003 and a survey 3 years after this disaster found that for over half the survey respondents (56.4%, n = 272) the bushfire did not have a lasting effect on their overall health and 2.5% (n = 12) reported that their overall health was better than before (18).…”
Section: Discussionmentioning
confidence: 99%
“…Whether smoke exposure occurs locally or downstream of a wildfire event, there is a growing body of data indicating that adverse health outcomes are possible in humans [ 48 ] as well as animals [ 49 ]. As an example of human effects, a cohort exposed to an intense and long-duration wildfire smoke event in Seeley Lake, Montana, experienced persistent lung function decrements that were measurable two years following exposure [ 50 ]. In cell models, wildfire smoke PM has been shown to induce inflammation and cytotoxicity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have shown air quality improving for the contiguous United States from the reduction of industrial and vehicular emissions 4 , 5 , air pollution in wildfire-prone areas, particularly in the mountain west region of the United States, has increased and is projected to further worsen due to climate-mediated increases in wildfire activity 6 – 8 . These communities impacted by wildfire smoke from nearby and distant wildfires experience high episodic exposures to PM 2.5 with concentrations often exceeding 24-hour ambient air quality standards for extended periods 9 , 10 .…”
Section: Background and Summarymentioning
confidence: 99%